TINDAK TUTUR DAN FUNGSI TUTURAN EKSPRESIF DALAM ACARA MATA NAJWA DI YOUTUBE: KAJIAN PRAGMANTIK - Indah Sulmayanti; Devi Mariyani; Dika Rianza; Miranda Sari (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study discusses speech acts and expressive speech functions in the Mata Najwa program on the Youtube channel as a form of digital communication based on video streaming. The background of the study is based on the phenomenon of the increasing use of digital media as a means of conveying public opinion, including in the form of critical discussions on social media and online channels. The Mata Najwa program was chosen because it consistently presents speakers from various backgrounds who are actively involved in social, political, and legal discussions, thus allowing the emergence of various types of speech acts, especially expressive speech. This study aims to describe the types of speech acts and analyze the forms and functions of expressive speech that appear in verbal interactions between speakers. This study uses a qualitative descriptive approach with listening, note-taking, and recording techniques. Data in the form of speech transcripts were collected from four episodes of Mata Najwa which were considered to contain expressive and socially relevant verbal interactions. The results of the study showed that locutionary, illocutionary, and perlocutionary utterances were found consistently in each episode, while the dominant forms of expressive utterances included criticizing, sarcasm, praise, complaining, apologizing, and expressing gratitude. These utterances not only function as a means of emotional expression and personal attitudes, but also as a tool of social influence that can shape public opinion and strengthen criticism of current issues. Thus, this study concludes that the Mata Najwa program is not only a medium for entertainment and information, but also plays a role as a public communication forum that is full of pragmatic values and is relevant to be analyzed in linguistic and social contexts.